(3GdHUGFQ hGdPNGFQs - (3Ydj Hf eMeO Hf GdYHGS GdJhMjOj, CHh MjGf,J (B400 (3g` s
(3ChdgG (B:s
(3Gddge GLYd ZOhfG Edjc ebQhfG HGdJhcd Ydjc gPG GdLRA GdNGeS ef GdHUGFQ , hgh Ufh eG Sda efg s
(3BNQ GdfSNI ZjQ hGVM GdJUhjQs
(3ef GdfSNI GdSGHbI BNQ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B205 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B684s
Keywords: (3GdCOHs